A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages Again, many existing services are provided — and excellently provided — by local authorities. But these services have grown up piecemeal to meet different needs at different times, and so they are usually conducted as separate and independent services. There is no sufficient link either between these services themselves or between them and general medical practice and the hospitals. Need for a new attitude Perhaps the most important point of all is the need for a new attitude towards health care. Personal health still tends to be regarded as something to be treated when at fault, or perhaps to be preserved from getting at fault, but seldom as something to be positively improved and promoted and made full and robust. Much of present custom and habit still centres on the idea that the doctor and the hospital and the clinic are the means of mending ill-health rather than of increasing good health and the sense of well-being. While the health standards of the people have enormously improved, and while there are gratifying reductions in the ravages of preventable disease, the plain fact remains that there are many men and women and children who could be enjoying a sense of health and physical efficiency which they do not in fact enjoy; there is much sub-normal health still, which need not be, with a corresponding cost in efficiency and personal happiness. Closing the gaps The Government's proposals for closing the gaps in the existing services and building a comprehensive National Service are described in the paragraphs which follow. For convenience, they are divided into four main sections dealing with General Medical Practice, Hospitals, Consultants, and Clinics and other Local Services. Short sections are added on Administration, on the Service in Scotland, and on Finance. Some of the proposals (e.g., a full dental or ophthalmic service) will take time to develop ; the full national service cannot be built in a day. But the important thing is to make sure that the design is sound. Some of the proposals are controversial - that is inevitable. The Government hope, however, that their proposals, modified where modifications can be shown to be improvements, will win the approval of all those who will look to the new scheme for the promotion of their health, and the goodwill of those on whose willing service its success will depend. II. GENERAL MEDICAL PRACTICE Principles of a General Practitioner Service The arrangements for general medical practice are the most important part of the proposals for a National Health Service. The family doctor is the first line of defence in the fight for good health ; it is to him that every citizen using the new service will look for advice on his own health and the health of his family ; and it is generally through him 5 36/H24/41